2020
DOI: 10.1093/jamia/ocaa252
|View full text |Cite
|
Sign up to set email alerts
|

Doctors documenting: an ethnographic and informatics approach to understanding attending physician documentation in the pediatric emergency department

Abstract: Objective The pediatric emergency department is a highly complex and evolving environment. Despite the fact that physicians spend a majority of their time on documentation, little research has examined the role of documentation in provider workflow. The aim of this study is to examine the task of attending physician documentation workflow using a mixed-methods approach including focused ethnography, informatics, and the Systems Engineering Initiative for Patient Safety (SEIPS) model as a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Similarly, body mapping can be used with community members to explore how to broader contextual factors shape health [35]. Other suggested methods include systems mapping [36], observations (including participant observation) [37], photo elicitation [38], and task analysis [39]. Mixed methods approaches should be incorporated to produce a comprehensive view of the topic being studied as well as to triangulate findings.…”
Section: Stage Of the Design Lifecyclementioning
confidence: 99%
“…Similarly, body mapping can be used with community members to explore how to broader contextual factors shape health [35]. Other suggested methods include systems mapping [36], observations (including participant observation) [37], photo elicitation [38], and task analysis [39]. Mixed methods approaches should be incorporated to produce a comprehensive view of the topic being studied as well as to triangulate findings.…”
Section: Stage Of the Design Lifecyclementioning
confidence: 99%
“…A longitudinal prospective design was used. ED work processes are complex and they cannot be measured with a single data point or by one statistical method but need to be explored from a combination of data gathered with multiple methods, and therefore, a sociotechnical systems framework and a mixed-methods approach have been suggested for implementing larger information technology projects [33]. Also, a longer-term fol-low-up on the effects of system implementation is recommended as a systematic review indicated that EHR system implementation first increased documentation time, but as staff become more familiar with the system it ultimately improved work flow [13].…”
Section: Designmentioning
confidence: 99%